KEBIJAKAN OPTIMASI PAJAK PENGHASILAN DALAM KEGIATAN E-COMMERCE - Cahyadini, Amelia; Oka Margana, Indra (Veritas et Justitia, 2018)
E-commerce poses a challenge to establishing a viable tax system.  The Indonesian Directorate General of Taxes have yet to establish a viable data collection system on the number of active e-commerce business persons and how much they earn annually.  The main question to be discussed here is how tax income regulation in Indonesia responds to e-commerce activities, taking into consideration the existing self-assessment system? The author shall attempt to answer this question by using a juridical normative approach. This research leads to one recommendation, i.e. to improve government revenue from e-commerce tax in Indonesia a rule should be established obligating e-commerce actors to obtain certificate of reliability (trust mark). This will improve government and public monitoring capability.